The sociology of globalization - Martell, Luke (polity, 2010)
"This accessible and wide-ranging book demonstrates the distinctive insights that sociology has to bring to the study of globalization. Taking in the cultural, political and economic dimensions of globalization, the book provides a thorough introduction to key debates and critically evaluates the causes and consequences of a globalizing world." "In addition to topics such as America's changing position in the world under President Obama, the growth of China as a global power and anti-globalization movements, Martell brings to the discussion other aspects of world affairs that sociologists have sometimes not focused on so much. In doing so, he underlines the importance of economic motivations and structures, and shows how power, inequality and conflict are major factors in globalization. The book argues that globalization offers many opportunities for greater interaction and participation in societies throughout the world, for instance through the media and migration, but also has dark sides such as war and nuclear proliferation, global poverty, climate change and financial crisis."--BOOK JACKET